MENELAAH KONSEP-KONSEP DASAR ORGANISASI - Mohamad Muspawi; Salsabila Janati; Keiza Panjaitan; Julia Dwi Mawarni (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study discusses the basic concepts of the organization. As for the purpose of this study is tobe able to find out what is included in the scope of the basic concept of the organization, which will then be described and explained in more detail. The method used in this research is aqualitative method whit a literature study approach, while the literature used is by utilizing digital literacy and other data that containsthe object under study. The result of the research show that the organization is so important for human life and human civilization in living their daily lives to fulfil their needs and desires, therefore it is very important for us to understand the basic concepts of the organization, so that in the creation and implementation of the organization formed it can be carried out in the best possible way. Furthermore, what will be the main topic of discussion in this research is the definition of organization, organizational principles, organizational forms and organizational   structure.Keywords: Organizational concept, Organizational basic, Organization